2009
DOI: 10.1049/el.2009.1305
|View full text |Cite
|
Sign up to set email alerts
|

150 GHz of thermo-optic tuning in direct UV written silica-on-silicon planar Bragg grating

Abstract: An integrated direct UV written apodised planar Bragg grating reflector with 154 GHz (1.23 nm) of thermo-optic tuning in the C-band and a response speed 31 GHz/ms is demonstrated. The degree and speed of tuning of the fabricated device indicates potential application in dynamic optical networks, as an optical add-drop multiplexer.Introduction: An optical add-drop multiplexer (OADM) is a fundamental device in dense wavelength division multiplexing (DWDM) networks. Control over the spectral response of an OADM i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 15 publications
3
15
1
Order By: Relevance
“…Bulk heating experiments show that α + ς is approximately 10 pm/K in silica-on-silicon substrate in the 1550 nm wavelength region. This provides a tuning range of 154 GHz and a response speed of 31 GHz/ms [17]. In this work the thermal tuning of the micro heaters exhibits similar behaviors during the experiments.…”
Section: B Thermal Tuningmentioning
confidence: 52%
See 1 more Smart Citation
“…Bulk heating experiments show that α + ς is approximately 10 pm/K in silica-on-silicon substrate in the 1550 nm wavelength region. This provides a tuning range of 154 GHz and a response speed of 31 GHz/ms [17]. In this work the thermal tuning of the micro heaters exhibits similar behaviors during the experiments.…”
Section: B Thermal Tuningmentioning
confidence: 52%
“…It has been previously demonstrated that silica-on-silicon planar Bragg gratings fabricated by direct UV writing technique can be thermally tuned [17]. It shows that the phase shift ΔλB caused by thermal tuning is proportional to Bragg wavelength λB and can be expressed as :…”
Section: B Thermal Tuningmentioning
confidence: 99%
“…Additionally a Bragg grating was defined away from bridge structure to monitor thermal fluctuations for the bulk chip. Both Bragg gratings were fabricated using direct UV writing (DUW) after the fiber was bound to the wafer [25][26][27] using FHD. FHD silica soot was formed through burning precursors of SiCl 4 , PCl 3 and BCl 3 at flow rates of 139, 31 and 70 sccm respectively, using the torch configuration illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the next evolution of the system, we propose that the MZI is miniaturised by incorporating it onto a silicon photonics platform [12]. This should improve stabilisation and reduce the time taken to thermally tune the path difference to within tens of milliseconds [13].…”
Section: Discussionmentioning
confidence: 99%